Unraveling the riverine antibiotic resistome: The downstream fate of anthropogenic inputs. (1st June 2021) - Lee, Jangwoo; Ju, Feng; Maile-Moskowitz, Ayella; Beck, Karin; Maccagnan, Andreas; McArdell, Christa S.; Dal Molin, Marco; Fenicia, Fabrizio; Vikesland, Peter J.; Pruden, Amy; Stamm, Christian; Bürgmann, Helmut
Highlights: Initial rapid decrease of wastewater-borne resistance levels is primarily explained by dilution Additional source/sink effects become apparent over longer downstream distances Correct evaluation of resistance determinant fate requires mass-transport analysis bacA was prevalent in less-disturbed waters proving its high natural prevalence Abstract: River networks are one of the main routes by which the public could be exposed to environmental sources of antibiotic resistance, that may be introduced e.g. via treated wastewater. In this study, we applied a comprehensive integrated analysis encompassing mass-flow concepts, chemistry, bacterial plate counts, resistance gene quantification and shotgun metagenomics to track the fate of the resistome (collective antibiotic resistance genes (ARGs) in a microbial community) of treated wastewater in two Swiss rivers at the kilometer scale. The levels of certain ARGs and the class 1 integron integrase gene ( intI1 ) commonly associated with anthropogenic sources of ARGs decreased quickly over short distances (2-2.5 km) downstream of wastewater discharge points. Mass-flow analysis based on conservative tracers suggested this decrease was attributable mainly to dilution but ARG loadings frequently also decreased (e.g., 55.0-98.5 % for ermB and tetW ) over the longest studied distances (6.8 and 13.7 km downstream). Metagenomic analysis confirmed that ARG of wastewater-origin did not persist in rivers after 5 6.8 km downstream distance. sul1 and intI1 levels and loadings were more variable and even increased sharply at 5 6.8 km downstream distance on one occasion. While input from agriculture and in-situ positive selection pressure for organisms carrying ARGs cannot be excluded, in-system growth of biomass is a more probable explanation. The potential for direct human exposure to the resistome of wastewater-origin thus appeared to typically abate rapidly in the studied rivers. However, the riverine aquatic resistome was also dynamic, as evidenced by the increase of certain gene markers downstream, without obvious sources of anthropogenic contamination. This study provides new insight into drivers of riverine resistomes and pinpoints key monitoring targets indicative of where human sources and exposures are likely to be most acute. Graphical abstract: Image, graphical abstract